2017
DOI: 10.1186/s12884-017-1362-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-malarial infectious diseases of antenatal care in pregnant women in Franceville, Gabon

Abstract: BackgroundIn sub-tropical countries, infectious diseases remain one of the main causes of mortality. Because of their lack of active immunity, pregnant women and their unborn children represent the most susceptible people. In Gabon, data on infectious diseases of pregnant women such as syphilis and rubella are either scarce or very old. Few studies have assessed T. gondii infection during pregnancy in the country. Here, we evaluate seroprevalence of HIV, HTVL-1, syphilis and T. gondii and rubella infection dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…These data confirm the high prevalence of HTLV-1 in Gabon and extend it to most rural areas, since we studied adult populations of both sexes, from 6 of the 9 rural provinces of this country. Previous studies mainly carried out in pregnant women or in populations from some regions of Gabon (mostly Franceville area and/or Eastern Gabon regions), have observed a high level of HTLV-1 infection [ 18 21 , 24 , 25 ]. However, such studies were mostly based on serological analyses with, for the oldest studies, Western blot interpretation criteria that are now considered as poorly specific.…”
Section: Discussionmentioning
confidence: 99%
“…These data confirm the high prevalence of HTLV-1 in Gabon and extend it to most rural areas, since we studied adult populations of both sexes, from 6 of the 9 rural provinces of this country. Previous studies mainly carried out in pregnant women or in populations from some regions of Gabon (mostly Franceville area and/or Eastern Gabon regions), have observed a high level of HTLV-1 infection [ 18 21 , 24 , 25 ]. However, such studies were mostly based on serological analyses with, for the oldest studies, Western blot interpretation criteria that are now considered as poorly specific.…”
Section: Discussionmentioning
confidence: 99%
“…We found that age groups 20-24, 25-29, and having no selfreported RCV history increased seronegativity. The youngest age group showed the highest seronegativity in previous studies during the pre/post-RCV era, 3,17,[32][33][34] indicating cumulative opportunities to be exposed to rubella virus or vaccination by age. However, younger age did not influence increased seronegativity in other studies, both before and after RCV initiation, 15,35,36 depending on the timing of rubella epidemics and the difference in vaccine coverage of each age group after changing the vaccine strategy in each country.…”
mentioning
confidence: 75%
“…Some factors, including maternal education, maternal occupation, residential area, para, number of antenatal care visit, mode of delivery, baby's sex, low birth weight, and preterm birth, might be less relevant for rubella seronegativity in this study, while some of these were discussed as the relevant factors in previous studies. 3,17,34,[36][37][38][39] A limitation of the present study is that we could not discuss the effect of RCVs on the rubella seronegativity sufficiently due to the unavailability of individual vaccination record to confirm the self-reported RCV history. This study described the CRS incidence and rubella seronegativity that was reported a relatively short time after the previous rubella outbreak and vaccine introduction.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…In the United States, the incidence of congenital syphilis increased from 8.4 per 100,000 in 2012 to 11.6 per 100,000 live births in 2014, reflecting the increase in disease among pregnant women 5 . In a municipality in Gabon, a country in the African continent, a study with 973 pregnant women found a prevalence of 2.5% for syphilis, 4.0% for HIV infection and 57.3% for toxoplasmosis 6 .…”
Section: Introductionmentioning
confidence: 99%